Recognizing Each Student's Unique Learning Style: Adapting the Brain-Based Learning Approach in Natural and Social Science Learning - Thariq Al Ayubi; Hanif Al Kadri; Yanti Fitria; Ulfia Rahmi (Jurnal Penelitian Pendidikan IPA, 2024)
This study developed a brain-based learning (BBL) model that is adapted to students' learning styles to improve learning outcomes in Natural and Social Sciences in elementary schools. Using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development method, this research produced a learning module that was validated by material, media, and language experts, and tested for practicality and effectiveness in two schools. The results showed a significant increase in post-test scores compared to the pre-test, indicating that the BBL approach was effective in supporting students' understanding. The main conclusion of this study is that the adaptive BBL model is able to create a more inclusive learning environment and support individual cognitive needs, thus improving students' understanding and retention of information.